2019
DOI: 10.1128/jvi.00558-19
|View full text |Cite
|
Sign up to set email alerts
|

K63-Linked Ubiquitin Is Required for Restriction of HIV-1 Reverse Transcription and Capsid Destabilization by Rhesus TRIM5α

Abstract: TRIM5␣ is an antiviral restriction factor that inhibits retroviral infection in a species-specific fashion. TRIM5␣ binds to and forms assemblies around the retroviral capsid. Following binding, poorly understood, ubiquitin-dependent events lead to the disassembly of the viral core, prior to the accumulation of viral reverse transcription products in the target cell. It is also known that assemblies of TRIM5␣ and other TRIM family proteins can be targets of autophagic degradation. The goal of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 60 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…However, Trim16 did not show any significant regulation of Prdx1 ubiquitination (Figure 6A and S7A). Notably, when the ubiquitinating activity of Trim16 was removed (Trim16-DUB [Trim16-deubiquitinase fusion proteins]; Figure 6B), 35,36 the effective regulatory effect of Trim16 on Prdx1 phosphorylation almost completely disappeared (Figure 6C). These The E3 ligase activity-dependent Trim16-mediated inhibition of Prdx1 phosphorylation suggested that there might be other key proteins, particularly kinases, mediating the Trim16-Prdx1 interaction (Figure 6D).…”
Section: Trim16 Inhibits Prdx1 Phosphorylation By Promoting Src Degra...mentioning
confidence: 99%
“…However, Trim16 did not show any significant regulation of Prdx1 ubiquitination (Figure 6A and S7A). Notably, when the ubiquitinating activity of Trim16 was removed (Trim16-DUB [Trim16-deubiquitinase fusion proteins]; Figure 6B), 35,36 the effective regulatory effect of Trim16 on Prdx1 phosphorylation almost completely disappeared (Figure 6C). These The E3 ligase activity-dependent Trim16-mediated inhibition of Prdx1 phosphorylation suggested that there might be other key proteins, particularly kinases, mediating the Trim16-Prdx1 interaction (Figure 6D).…”
Section: Trim16 Inhibits Prdx1 Phosphorylation By Promoting Src Degra...mentioning
confidence: 99%
“…It is known that premature uncoating disrupts viral DNA synthesis resulting in reverse transcription inhibition [131]. Thus, ubiquitin ligase activity of TRIM5α allows the inhibition of reverse transcription [81,130,132]. Alternatively, TRIM5α has also a key role in the activation of innate immune response through its ubiquitin ligase activity [6,130].…”
Section: Trim5α Exerts Its Antiviral Activity Through Auto-polyubiquitinationmentioning
confidence: 99%
“…Ubiquitination of Trim5α prevents the build-up of reverse transcripts, and proteasomal inhibition abrogates that activity [ 69 ]. The ubiquitination of Trim5α also induced the classic premature disassembly of viral cores, while Trim5α conjugated with a ubiquitinase had no such effect [ 71 ].…”
Section: Structures Of the Capsid In Complex Host Cell Factorsmentioning
confidence: 99%